'Collaboration' in Contemporary Music: A Theoretical View. Issue 6 (1st November 2016) - Taylor, Alan
Abstract : Contemporary composers frequently find themselves working with other artists in composing. The paper presents a framework which aims to provide a better understanding of the working relationships found in such situations, and the factors which affect the type of working relationships which develop. A distinction is drawn between dialogic creative activity—the universal situation of creating in a context—and creating with others actually present. Four different types of relationship which develop when working directly with others are defined. This typology can help in the better understanding of the relationships which composers establish and can act as a stimulus to the review and further development of compositional practice. The relationship between the language of an art form and the language used for communication between creative partners is identified as a key factor in affecting the type of working relationships which develop between artists.